Rethinking Early Childhood Education Management: Its Role in Strengthening Administrative Effectiveness - Susanti, Katerina; Rasyid, Abdul; Usgianti, Rivana (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2026)
This study examines the role of educational management in strengthening administrative effectiveness in early childhood education (ECE) institutions. While previous studies have often treated educational management as a linear predictor of institutional outcomes, this study adopts a governance perspective to better understand how management practices operate within context-specific conditions. Focusing on ECE institutions in Indragiri Hilir Regency, Indonesia, this research also considers the role of community-based actors, particularly Bunda PAUD, as part of localized educational governance. A quantitative approach was employed using a simple linear regression model. Data were collected from 40 respondents, including school principals and teachers selected through purposive sampling. The research instrument was a Likert-scale questionnaire measuring early childhood education management and administrative effectiveness. Data were analyzed using validity and reliability tests, regression analysis, t-test, and coefficient of determination (R²). The findings indicate that early childhood education management has a positive and statistically significant effect on administrative effectiveness (β = 0.672; p < 0.05), with a coefficient of determination of 0.64. This suggests that management practices account for 64% of the variance in administrative effectiveness. However, both variables were found to be at a moderate level, indicating that management practices and administrative systems are not yet fully optimized. The results also highlight that administrative effectiveness is influenced not only by management but also by contextual factors such as infrastructure, institutional capacity, and stakeholder involvement. This study contributes to the literature by rethinking educational management as a dynamic and context-sensitive process while integrating a governance perspective that emphasizes the role of localized community actors. The findings provide practical implications for strengthening managerial capacity, enhancing stakeholder collaboration, and improving administrative systems in early childhood education.